The Role of the Corporate Penalty System on Environmental Regulation - Torodji, Rais; Hartiwiningsih, Hartiwiningsih; Handayani, I Gusti Ayu Ketut Rachmi; Nur, Muhammad (Journal of Human Rights, Culture and Legal System, 2023)
Criminal acts Indonesia's environmental law has numerous issues and has long been regulated in Indonesia. However, the question is whether the Corporate Penalty System on Environmental Regulation can implement this policy. This research aims to analyze the role of the corporate penalty system in environmental regulation. This is normative legal research with secondary data from primary, secondary, and tertiary legal materials. The research results show, first, that the Corporate Penalty System on Environmental Regulation has overlapping regulations and the need for more clarity regarding corporate punishment, substantive issues, and law enforcement. The Indonesian government must focus on this to achieve an integrated corporate punishment system. In environmental regulations, the overlapping provisions of administrative and criminal law contribute to the unjust nature of the corporate punishment system. Therefore, it tends to vary from one location to the next. Second, the threat of punishment is not proportional to the heinousness of the act. Third, the absence of harmonization with prior legal arrangements resulted in disparate sentences. The best way to enforce environmental crimes committed by corporations is to have adequate regulations to work from; encouraging harsher penalties for social and economic losses will be detrimental to environmental justice; and implementing an integrated system of corporate punishment requires a variety of measures, such as enacting new regulations and focusing on ecological criminal law enforcement.